The Application of the Bushido – Samurai Code Principles within Romanian Companies - Nobumichi Watahik; Yoshikazu Matsui; Violeta Mihaela Dincă; Iulia Waniek (Amfiteatru Economic)
Holding a managerial position within a company in 2019 is a challenging task and within this period the business climate is a dynamic one. When conceiving rightful strategies, managers should take into account every detail regarding the fast-changing Romanian business environment. Bushido is one of the oldest moral systems in Japan and refers to a code of honour and standards that commanded the samurai way of life and these principles advanced by Bushido are still worthy in several corporate systems. Several studies showed how using the attributes of ‘Bushido’ can lead managers to become more effective and prosperous in their business and can help them establish and maintain a credible image within the industry. For this study, interviews were taken in order to obtain the views of the representatives of 37 corporations in Romania and the objectives of the study were to: (1) To assess which canons of Bushido are being implemented by managers within the Romanian contemporary businesses and are applicable to business context analysis, strategic enforcement & control and development of business partnerships and collaborations, (2) To determine if and how the extent of incorporating Bushido’s principles within the management strategies and operations of companies has an effect on the company’s success’ factors. The achieved results of this study can be mentioned as follows. 1. The Bushido code is being integrated within the Romanian contemporary organizations’ management and business relationships with other firms. The paper revealed that for almost all the managers included in the sample there were recorded notable interrelationships between the Bushido principles and the managers’ goals in the sense that if they apply the Bushido principles on a higher and more developed level, it will be less difficult for them to attain their strategic objectives. 2. The most significant factors leading to business success achievement obtained due to the application the Bushido principles within the business processes of the companies were indicated as: the growth of the company’s and manager’s image and professional reputation; prestige and good attitude from the stakeholders; a boost within the research and development process and the raise of the quality of business relationships